Conductive paste and preparation method and application thereof
By adding onion-like fullerenes in the dispersion process of carbon nanotubes and optimizing the preparation method of dispersant gel liquid, the problem of poor storage stability of carbon nanotubes in the prior art is solved, and efficient dispersion of carbon nanotubes and Maintenance of conductivity.
Patent Information
- Application Number
- CN202411614698.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-02-18
AI Technical Summary
It is difficult to prepare carbon nanotube slurry with single-wall carbon nanotubes as the main component of good storage stability, and excessive dispersion will lose the conductive properties of the carbon nanotubes.
By adding a small amount of onion-like fullerene during the dispersion of carbon nanotubes and optimizing the preparation method of dispersant gel liquid, including high-speed dispersion and controlling the molecular weight distribution, the dispersion of carbon nanotubes and the storage stability of the slurry is improved.
The longer tube length of carbon nanotubes is effectively retained, the storage stability of the slurry is improved, the viscosity change rate is reduced, and the conductivity is maintained.
Smart Images

Figure CN119480214A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of carbon nanotubes, and in particular to a conductive paste and a preparation method and application thereof. Background Art
[0002] Carbon nanotubes (CNTs) are mainly composed of several to dozens of layers of coaxial circular tubes composed of carbon atoms arranged in a hexagonal pattern. The diameter of the tube is generally 2-100 nanometers and the length can reach 10-50 microns. Carbon nanotubes stand out among various carbon nanomaterials for their excellent electrical conductivity, thermal conductivity and good mechanical strength. In particular, they are widely used as conductive agents in the lithium battery industry for their excellent electrical conductivity. For carbon nanotubes, they are divided into single-walled carbon nanotubes (SWCNTs), double-walled carbon nanotubes and multi-walled carbon nanotubes according to the number of coaxial carbon nanotube walls.
[0003] Compared with multi-walled carbon nanotubes, SWCNTs have a smaller diameter distribution range, the tube length may reach tens of microns to hundreds of microns, the carbon tubes have fewer defects, and the G / D ratio ranges as high as 40-150; they have excellent electrical and thermal conductivity, optical properties, thermal stability, high strength and toughness, and are currently gradually used in the positive electrode materials of lithium-ion batteries. The main functions of SWCNTs in positive electrode materials are: 1) SWCNTs have good electrical conductivity, and a very low addition amount can improve the conductivity of the electrode, thereby reducing the internal resistance of the battery; 2) SWCNTs have a long tube length, and adding them can improve the stability of the positive electrode material during the cycle, reduce the shedding of active substances and structural damage, and improve the cycle stability of the battery; 3) SWCNTs have high mechanical strength and thermal stability, which can restrain the positive electrode material to a certain extent, reduce the volume expansion and contraction during the charge and discharge process, and extend the battery life; 4) SWCNTs have a large relative area and can provide more active sites, which helps to increase the electrochemical reaction rate and lithium ion diffusion rate of the positive electrode material; 5) The addition of SWCNTs is beneficial to increase the specific capacity of the positive electrode material and help to increase the energy density of the battery.
[0004] Due to the large specific surface area of SWCNTs, it is difficult to disperse them. Strong shear premixing and high-pressure homogenization are usually used for dispersion. However, excessive dispersion will cause a sharp decrease in the length of the single-walled tube and lose the conductive properties of the carbon nanotubes. In addition, the higher the concentration of SWCNTs, the greater the viscosity of the prepared slurry. If the dispersion is not good, the slurry will have a large change in viscosity or liquid precipitation after long-term storage. Therefore, it is of great significance to study a carbon nanotube slurry with a long tube length and stable storage performance, which is mainly composed of SWCNTs. Summary of the invention
[0005] In view of the deficiencies in the prior art, an object of the present invention is to provide a conductive paste with good storage stability and a preparation method and application thereof.
[0006] Solutions for solving problems
[0007] In a first aspect, the present invention provides a conductive paste, wherein the conductive paste comprises the following components in percentage by weight, based on the total weight of the conductive paste being 100%:
[0008] Carbon nanotubes 0.45%-1.35%
[0009] Onion-like fullerene 0.02%-0.15%
[0010] Dispersant glue 12%-45%
[0011] The balance was solvent 1.
[0012] Preferably, based on the total mass of the conductive paste being 100%, the conductive paste comprises the following components in percentage by mass:
[0013] Carbon nanotubes 0.6%-1.30%
[0014] Onion-like fullerene 0.02%-0.1%
[0015] Dispersant glue 12.5%-37.5%
[0016] The balance was solvent 1.
[0017] Preferably, the onion-like fullerene has an outer diameter of 5-80 nm and an inner diameter of 2-72 nm.
[0018] Preferably, the onion-like fullerene has 3 to 10 layers and a specific surface area of 80 to 500 m 2 / g,I G / I D Is 1-5.
[0019] Preferably, the carbon nanotubes include single-walled carbon nanotubes and / or multi-walled carbon nanotubes.
[0020] Preferably, the carbon nanotubes are a mixture of single-walled carbon nanotubes, double-walled carbon nanotubes and triple-walled carbon nanotubes.
[0021] Preferably, the mass proportion of the single-walled carbon nanotubes is 70-95%, the mass proportion of the double-walled carbon nanotubes is 4-25%, and the mass proportion of the triple-walled carbon nanotubes is 1-5%.
[0022] Preferably, the length of the carbon nanotubes in the conductive paste is 20-60 μm.
[0023] Preferably, the dispersant gel solution contains a dispersant.
[0024] Preferably, the dispersant glue solution comprises a dispersant and a solvent 2.
[0025] Preferably, the dispersant in the dispersant colloid is selected from polyvinylidene fluoride.
[0026] Preferably, the mass percentage of the dispersant in the dispersant colloid is 6-10%, and the weight average molecular weight of the dispersant in the dispersant colloid is 400000-1000000 g / mol.
[0027] Preferably, the polydispersity coefficient of the dispersant in the dispersant colloid is 1.5-2.5.
[0028] Preferably, the viscosity of the dispersant colloid is 3000-8000cps.
[0029] Preferably, the solvent 1 and the solvent 2 are independently selected from N-methylpyrrolidone.
[0030] Preferably, the viscosity of the conductive paste is 6000-13000 cps, and D90 of the conductive paste is less than or equal to 60 μm.
[0031] Preferably, after being stored at room temperature for 3 months, the viscosity change rate of the conductive paste is less than 30%, and the D90 change rate of the conductive paste is less than 50%.
[0032] In a second aspect, the present invention provides a method for preparing the conductive paste as described in any one of the above items, the preparation method comprising:
[0033] (1) mixing a dispersant gel, onion-like fullerene, and solvent 1 and pre-dispersing them to obtain a pre-dispersed liquid;
[0034] (2) The carbon nanotubes are mixed with the pre-dispersed liquid, and then pre-mixed and homogenized to obtain the conductive paste.
[0035] In some embodiments, in step (1), the preparation method of the dispersant colloid comprises: dissolving the dispersant in solvent 2, and obtaining the dispersant colloid after stirring and high-speed dispersion;
[0036] The high-speed dispersion pressure is 50-120 MPa, and the high-speed dispersion is performed 1-6 times.
[0037] Preferably, the initial weight average molecular weight of the dispersant is 600,000-1,200,000 g / mol.
[0038] Preferably, before the stirring, the polydispersity coefficient of the dispersant in the solution is 2.5-5.5.
[0039] Preferably, the solvent 1 and the solvent 2 are independently selected from N-methylpyrrolidone.
[0040] Preferably, in step (1), the linear speed of the premix is controlled to be 10-30 m / s and the time is 10-20 min.
[0041] Preferably, in step (2), the linear speed of the premix is controlled to be 20-80 m / s and the time is 10-20 min.
[0042] Preferably, the homogenization pressure is 20-60 MPa, and the number of times is 4-15 times.
[0043] In a third aspect, the present invention provides a conductive film, wherein the conductive film comprises the conductive paste described in any one of the above items or the conductive paste obtained by any one of the above preparation methods.
[0044] Preferably, the volume resistivity of the conductive film is 15-40Ω.cm.
[0045] In a fourth aspect, the present invention provides a lithium-ion battery, wherein the lithium-ion battery comprises the conductive paste described in any one of the above items or the conductive paste obtained by any one of the above preparation methods.
[0046] Effects of the Invention
[0047] The present invention adds a small amount of onion-shaped fullerenes during the dispersion process of carbon nanotubes with SWCNTs as the main component. The onion-shaped fullerenes can play a role similar to "nano balls" to buffer the damage of excessive dispersion to carbon nanotubes, so that the carbon nanotubes retain a longer tube length; in addition, the onion-shaped fullerenes with a hollow structure are small in size and are evenly distributed between the carbon nanotube bundles, which can effectively prevent the re-agglomeration problem of the carbon nanotube bundles after dispersion, thereby improving the storage stability of the slurry; at the same time, the present invention optimizes the storage stability of the conductive slurry by optimizing the method for preparing the dispersant colloid. Specifically, the present invention performs high-speed dispersion of the dispersant, reduces the initial viscosity of the dispersant colloid, and optimizes the uniformity of the molecular weight distribution of the dispersant, thereby improving the dispersibility coefficient (weight average molecular weight / number average molecular weight) of the dispersant. Therefore, in the subsequent slurry dispersion, the dispersibility of the dispersant to the carbon nanotubes is improved, so that the storage stability of the final conductive slurry is improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] Figure 1 This is the TEM morphology of the onion-shaped fullerene powder in Example 1 of the present invention;
[0049] Figure 2 This is a SEM image of carbon nanotubes and onion-like fullerenes in the conductive paste in Example 1 of the present invention;
[0050] Figure 3This is a SEM image of carbon nanotubes and onion-like fullerenes in the conductive paste in Example 2 of the present invention;
[0051] Figure 4 This is a SEM image of carbon nanotubes in the conductive paste in Comparative Example 1 of the present invention;
[0052] Figure 5 This is a SEM image of carbon nanotubes and onion-like fullerenes in the conductive paste in Comparative Example 2 of the present invention;
[0053] Figure 6 TEM image of carbon nanotubes and onion-like fullerenes in the conductive paste in Example 1 of the present invention;
[0054] Figure 7 TEM image of carbon nanotubes and onion-like fullerenes in the conductive paste in Example 2 of the present invention;
[0055] Figure 8 TEM image of carbon nanotubes and onion-like fullerenes in the conductive paste in Comparative Example 2 of the present invention;
[0056] Fig. 9 The curves of storage time and viscosity of the conductive paste at room temperature in different embodiments and comparative examples of the present invention are shown;
[0057] Fig.10 The graphs are the change curves of the room temperature storage time and the D90 of the conductive paste in different embodiments and comparative examples of the present invention. DETAILED DESCRIPTION
[0058] In order to make the technical scheme and beneficial effects of the present invention more obvious and easy to understand, the following is described in detail by combining the accompanying drawings and listing specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples without specifying specific conditions are usually based on conventional experimental conditions. The reagents and raw materials used in the present invention are commercially available unless otherwise specified.
[0059] In the following description, a large number of specific details are given to provide a more thorough understanding of the present application. However, it is obvious to those skilled in the art that the present application can be implemented without one or more of these details. In other examples, in order to avoid confusion with the present application, some technical features known in the art are not described; that is, all features of the actual embodiments are not described here, and well-known functions and steps are not described in detail.
[0060] The purpose of the terms used herein is only to describe specific embodiments and is not intended to be limiting of the present application. When used herein, the singular forms "one", "an" and "said / the" are also intended to include plural forms, unless the context clearly indicates otherwise. It should also be understood that the terms "consisting of" and / or "comprising", when used in this specification, determine the presence of the features, integers, steps, operations, elements and / or parts, but do not exclude the presence or addition of one or more other features, integers, steps, operations, elements, parts and / or groups. When used herein, the term "and / or" includes any and all combinations of the relevant listed items.
[0061] Unless otherwise defined, technical and scientific terms used in this application have the same meanings as those in the technical field to which this application belongs.
[0062] If no specific techniques or conditions are specified in the following examples, the conventional techniques or conditions described in the literature in the art, or the conditions recommended by the product instructions and the manufacturer are generally used. The numerical ranges in the following examples all include the endpoint values.
[0063] Carbon nanotubes have broad application prospects in the fields of electronics, energy, medical treatment and environmental protection due to their unique physical and chemical properties, such as high conductivity, high strength and high specific surface area, especially in the field of lithium batteries. However, there are strong van der Waals attractions between carbon nanotubes, so that carbon nanotubes are not easily dispersed in solvents, and the stability of dispersed carbon nanotubes is poor. Therefore, the inventors of the present invention have proposed a conductive slurry containing a specific content of carbon nanotubes, onion-like fullerenes, a dispersant and a solvent after extensive and in-depth research, thereby improving the storage stability of the conductive slurry. Based on this, the present invention is proposed.
[0064] In a first aspect, the present invention provides a conductive paste, wherein the conductive paste comprises the following components in percentage by weight, based on the total weight of the conductive paste being 100%:
[0065] Carbon nanotubes 0.45%-1.35%
[0066] Onion-like fullerene 0.02%-0.15%
[0067] Dispersant glue 12%-45%
[0068] The balance was solvent 1.
[0069] In some embodiments, the mass percentage of carbon nanotubes in the conductive paste is 0.5%-1.35%, for example 0.6%, 0.65%, 0.7%, 0.75%, 0.8%, 0.85%, 0.9%, 0.95%, 1.0%, 1.05%, 1.1%, 1.15%, 1.2%, 1.25%, 1.3%, etc.
[0070] In some embodiments, in the conductive paste, the mass percentage of onion-like fullerene is 0.02%-0.14%, for example, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.11%, 0.12%, 0.13%, 0.14%, etc.
[0071] In some embodiments, in the conductive paste, the mass percentage of the dispersant colloid is 12.5%-45%, for example, 13%, 13.5%, 14%, 14.5%, 15%, 15.5%, 16%, 16.5%, 17%, 17.5%, 18%, 18.5%, 19%, 19.5%, 20%, 20.5%, 21%, 21.5%, 22%, 22.5%, 23%, 23.5%, 24%, 24.5%, 25%, 25.5%, 26%, 26.5%, 27%, 27.5%, 28%, 28.5%, 29%, 29.5%, 30%, 30.5%, 31%, 31.5%, 32%, 32.5%, 33%, 33.5%, 34%, 34.5%, 35%, 35.5%, 36%, 36.5%, 37%, 37.5%, 38%, 38.5%, 39%, 39.5%, 40%, 40.5%, 41%, 41.5%, 42%, 42.5%, 43%, 43.5%, 44%, 44.5%, etc.
[0072] In some embodiments, based on the total mass of the conductive paste being 100%, the conductive paste includes the following components in percentage by mass:
[0073] Carbon nanotubes 0.6%-1.30%
[0074] Onion-like fullerene 0.02%-0.1%
[0075] Dispersant glue 12.5%-37.5%
[0076] The balance was solvent 1.
[0077] In some embodiments, based on the total mass of the conductive paste being 100%, the conductive paste includes the following components in percentage by mass:
[0078] Carbon nanotubes 0.6~0.95%
[0079] Onion-like fullerene 0.03~0.05%
[0080] Dispersant glue 12.5%-25%
[0081] The balance was solvent 1.
[0082] In some embodiments, based on the total mass of the conductive paste being 100%, the conductive paste includes the following components in percentage by mass:
[0083] Carbon nanotubes 0.95%
[0084] Onion-like fullerene 0.05%
[0085] Dispersant glue 25%
[0086] The balance was solvent 1.
[0087] In some embodiments, the onion-like fullerene has an outer diameter of 5-80 nm (e.g., 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, 50 nm, 55 nm, 60 nm, 65 nm, 70 nm, 75 nm, 80 nm, etc.), and an inner diameter of 2-72 nm (e.g., 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, 50 nm, 55 nm, 60 nm, 65 nm, 70 nm, etc.).
[0088] In some embodiments, the outer diameter of the onion-like fullerene is 20-60 nm.
[0089] In some embodiments, the outer diameter of the onion-like fullerene is 20-50 nm.
[0090] In some embodiments, the inner diameter of the onion-like fullerene is 20-60 nm.
[0091] In some embodiments, the inner diameter of the onion-like fullerene is 25-60 nm.
[0092] In some embodiments, the onion-like fullerene has 3-10 layers (e.g., 3, 4, 5, 6, 7, 8, 9, 10, etc.) and a specific surface area of 80-500 m 2 / g(80m 2 / g, 85m 2 / g, 90m 2 / g, 95m 2 / g、100m 2 / g, 150m 2 / g, 200m 2 / g, 250m2 / g、300m 2 / g, 350m 2 / g, 400m 2 / g, 450m 2 / g、500m 2 / g, etc.), I G / I D is 1-5 (for example, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, etc.).
[0093] In some embodiments, the onion-like fullerene has 4-9 layers.
[0094] In some embodiments, the onion-like fullerene has a specific surface area of 150-400 m 2 / g.
[0095] In some embodiments, the onion-like fullerene has a specific surface area of 200-400 m 2 / g.
[0096] In some embodiments, the onion-like fullerene has a specific surface area of 250-400 m 2 / g.
[0097] In some embodiments, the onion-like fullerene G / I D Is 1-4.
[0098] Onion-like fullerene, also known as onion carbon, is a large carbon atom cluster composed of several concentric graphite shell layers with C60 as the core. The innermost layer is composed of 60 carbon atoms, and the number of carbon atoms in each layer is 60n. 2 (n is the number of layers) increases, and the spacing between layers is about 0.34nm. Onion-like fullerene has a unique hollow cage and concentric shell structure that gives it many special physical and chemical properties. Because it is spherical and has high mechanical strength and chemical inertness, it has been proven to have good lubricity. The present invention can effectively prevent the reagglomeration problem of SWCNTs bundles after dispersion by adding a certain amount of onion-like fullerene to the conductive slurry, thereby improving the storage stability of the slurry.
[0099] In some embodiments, the carbon nanotubes include single-walled carbon nanotubes and / or multi-walled carbon nanotubes.
[0100] In some embodiments, the carbon nanotubes are a mixture of single-walled carbon nanotubes, double-walled carbon nanotubes and triple-walled carbon nanotubes.
[0101] In some embodiments, the mass proportion of the single-walled carbon nanotubes is 70-95% (e.g., 71%, 72%, 73%, 74%, 75%, 76%, 77%, 78%, 79%, 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%, etc.), and the mass proportion of the double-walled carbon nanotubes is 4- 25% (for example, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, etc.), and the mass proportion of the triple-walled carbon nanotubes is 1-5% (for example, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, etc.).
[0102] In some embodiments, the mass percentage of the single-walled carbon nanotubes is 70-90%.
[0103] In some embodiments, the double-walled carbon nanotubes account for 10-25% by weight.
[0104] In some embodiments, the triple-walled carbon nanotubes account for 1.5-4.5% by weight.
[0105] In some embodiments, the carbon nanotubes in the conductive paste have a length of 20-60 μm.
[0106] In some embodiments, the dispersant gel comprises a dispersant.
[0107] In some embodiments, the dispersant gel solution comprises a dispersant and a solvent 2.
[0108] In some embodiments, the dispersant in the dispersant colloid is selected from polyvinylidene fluoride.
[0109] In some embodiments, the mass percentage of the dispersant in the dispersant colloid is 6-10% (for example, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, etc.), and the weight average molecular weight of the dispersant in the colloid is 400000-1000000 g / mol (for example, 500000 g / mol, 550000 g / mol, 600000 g / mol, 650000 g / mol, 700000 g / mol, 750000 g / mol, 800000 g / mol, 850000 g / mol, 900000 g / mol, 950000 g / mol, etc.).
[0110] In some embodiments, the mass percentage of the dispersant in the dispersant colloid is 6.5-10%.
[0111] In some embodiments, the weight average molecular weight of the dispersant in the dispersant gel is 600,000-900,000 g / mol.
[0112] In some embodiments, the polydispersity coefficient of the dispersant in the dispersant colloid is 1.5-2.5 (e.g., 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, etc.).
[0113] In some embodiments, the polydispersity coefficient of the dispersant in the dispersant gel is 1.6-2.3.
[0114] In some embodiments, the viscosity of the dispersant colloid is 3000-8000cps (e.g., 3500cps, 4000cps, 4500cps, 5000cps, 5200cps, 5400cps, 5600cps, 5800cps, 6000cps, 6500cps, 7000cps, 7500cps, etc.).
[0115] In some embodiments, the viscosity of the dispersant colloid is 4000-6000 cps.
[0116] In some embodiments, the solvent 1 is selected from N-methylpyrrolidone.
[0117] In some embodiments, the solvent 2 is selected from N-methylpyrrolidone.
[0118] In some embodiments, the viscosity of the conductive paste is 6000-13000 cps, and D90 of the conductive paste is less than or equal to 60 μm.
[0119] In some embodiments, after storage at room temperature for 3 months, the viscosity change rate of the conductive paste is less than 30%, and the D90 change rate of the conductive paste is less than 50%. In a second aspect, the present invention provides a method for preparing the conductive paste described in any one of the above, the preparation method comprising:
[0120] (1) mixing a dispersant gel, onion-like fullerene, and solvent 1 and pre-dispersing them to obtain a pre-dispersed liquid;
[0121] (2) The carbon nanotubes are mixed with the pre-dispersed liquid, and then pre-mixed and homogenized to obtain the conductive paste.
[0122] In some embodiments, in step (1), the preparation method of the dispersant colloid comprises: dissolving the dispersant in solvent 2, and obtaining the dispersant colloid after stirring and high-speed dispersion;
[0123] Wherein, the pressure of the high-speed dispersion is 50-120Mpa (for example, 55Mpa, 60Mpa, 65Mpa, 70Mpa, 75Mpa, 80Mpa, 85Mpa, 90Mpa, 95Mpa, 100Mpa, 105Mpa, 110Mpa, 115Mpa, 120Mpa, etc.), and the number of times the high-speed dispersion is performed is 1-6 times (for example, 1 time, 2 times, 3 times, 4 times, 5 times, 6 times, etc.).
[0124] In some embodiments, the initial weight average molecular weight of the dispersant is 600,000-1,200,000 g / mol (e.g., 650,000 g / mol, 700,000 g / mol, 750,000 g / mol, 800,000 g / mol, 850,000 g / mol, 900,000 g / mol, 950,000 g / mol, 1,000,000 g / mol, 1,100,000 g / mol, etc.).
[0125] In some embodiments, before the stirring, the polydispersity coefficient of the dispersant in the solution is 2.5-5.5 (e.g., 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 4, 4.5, 5, 5.5, etc.).
[0126] In some embodiments, the initial weight average molecular weight of the dispersant is 600,000-1,000,000 g / mol.
[0127] In some embodiments, in step (1), the linear speed of the premix is controlled to be 10-30 m / s (e.g., 10 m / s, 12 m / s, 14 m / s, 16 m / s, 18 m / s, 20 m / s, 22 m / s, 24 m / s, 26 m / s, 28 m / s, 30 m / s, etc.), and the time is 10-20 min (e.g., 10 min, 12 min, 14 min, 16 min, 18 min, 20 min, etc.).
[0128] In some embodiments, the solvent 1 is selected from N-methylpyrrolidone.
[0129] In some embodiments, the solvent 2 is selected from N-methylpyrrolidone.
[0130] In some embodiments, in step (2), the linear speed of the premix is controlled to be 20-80 m / s (e.g., 20 m / s, 22 m / s, 24 m / s, 26 m / s, 28 m / s, 30 m / s, 32 m / s, 34 m / s, 36 m / s, 38 m / s, 40 m / s, 42 m / s, 44 m / s, 46 m / s, 48 m / s, 50 m / s, 55 m / s, 60 m / s, 65 m / s, 70 m / s, 75 m / s, etc.), and the time is 10-20 min (e.g., 10 min, 12 min, 14 min, 16 min, 18 min, 20 min, etc.).
[0131] In some embodiments, the homogenization pressure is 20-60 MPa (e.g., 25 MPa, 30 MPa, 35 MPa, 40 MPa, 45 MPa, 50 MPa, 55 MPa, 60 MPa, etc.), and the number of times is 4-15 times (e.g., 4 times, 5 times, 6 times, 7 times, 8 times, 9 times, 10 times, 11 times, 12 times, 13 times, 14 times, 15 times, etc.).
[0132] In a third aspect, the present invention provides a conductive film, wherein the conductive film comprises the conductive paste described in any one of the above items or the conductive paste obtained by any one of the above preparation methods.
[0133] In some embodiments, the conductive film has a bulk resistivity of 15-40 Ω.cm.
[0134] In a fourth aspect, the present invention provides a lithium-ion battery, wherein the lithium-ion battery comprises the conductive paste described in any one of the above items or the conductive paste obtained by any one of the above preparation methods.
[0135] The technical solution of the present application is further described below in conjunction with a number of embodiments and comparative examples. In addition to the specific methods, equipment, and materials used in the embodiments, according to the technical personnel in this technical field's understanding of the prior art and the description of the present invention, any methods, equipment, and materials of the prior art that are similar or equivalent to the methods, equipment, and materials described in the embodiments of the present invention can also be used to implement the present invention. Unless otherwise specified, parts and percentages are parts by weight and weight percentages
[0136] Example 1
[0137] (1) Preparation of dispersant gel
[0138] 8 parts of dispersant (polyvinylidene fluoride, PVDF) powder with a weight average molecular weight of 950000 g / mol was added to 92 parts of NMP (N-methylpyrrolidone), and after simple mechanical stirring and mixing, it was dispersed twice with a homogenizer at 60 MPa to obtain an 8% dispersant gel.
[0139] The viscosity of the dispersant gel solution is 5800 cps. The weight average molecular weight of the dispersant in the gel solution measured by high performance liquid chromatography is 855000 g / mol, and the dispersion coefficient is 1.8.
[0140] (2) Preparation of conductive paste
[0141] After adding 25 parts of dispersant gel to 74 parts of NMP solvent, 0.05 parts of onion-like fullerene were added. The TEM image of the selected onion-like fullerene is shown in Figure 1 ,Depend on Figure 1 It can be seen that its structure is a hollow spherical structure with an outer diameter of 40nm, an inner diameter of 35nm, and a layer number n of 5; the BET (specific surface area) is 350m 2 / g;I G / I D The linear speed of the premixing equipment is 12 m / s, and the premixing time is 15 min to obtain a pre-dispersed liquid;
[0142] After 0.95 parts of carbon nanotubes were added to the pre-dispersed liquid, the pre-mixing equipment was used to pre-mix at 25m / s for 20min. After pre-mixing, the homogenization process was performed at a pressure of 40Mpa and the homogenization times were 10 times to obtain a carbon nanotube conductive slurry, wherein the carbon nanotube diameter was 1.5nm; BET was 900m 2 / g; the G / D ratio of the carbon nanotubes is 93; the purity of the carbon nanotubes is 99.5%. The composition of the selected carbon nanotubes is: 85% single-walled carbon nanotubes, 13% double-walled carbon nanotubes, and 2% triple-walled carbon nanotubes.
[0143] SEM images of carbon nanotubes and onion-like fullerenes in the conductive paste are shown in Figure 2 , TEM image see Figure 6 ,in Figure 2 The left picture in the middle is the SEM low-magnification morphology, and the right picture is the SEM high-magnification morphology. Figure 2 The left figure shows that the carbon nanotubes are relatively long, about 53 μm in length, and the bundle width is about 180 nm. Figure 2 The right picture shows that a small amount of onion-shaped fullerenes (in the red circle) are evenly distributed between the carbon nanotubes, with good dispersion and no agglomeration. They act as "nano balls" in the dispersion of carbon nanotubes, reducing the damage of the equipment to the carbon nanotubes and preventing the risk of reagglomeration of carbon nanotube bundles during subsequent storage.
[0144] Figure 6 The middle left picture is a TEM picture of the SEM low-magnification morphology, and the right picture is a TEM picture of the SEM high-magnification morphology. From the low-magnification morphology on the left, it can be seen that the onion-like fullerenes are evenly distributed between the carbon nanotubes; the high-magnification morphology on the right shows that the onion-like fullerenes are hollow spheres with an average size of 40nm and are well dispersed.
[0145] The length of the carbon nanotubes in the obtained carbon nanotube conductive slurry is about 53 μm, and the width of the tube bundle is about 180 nm. The G / D ratio after the slurry is dried is 76. The change curve of the storage time and viscosity of the conductive slurry at room temperature is shown in FIG. Fig. 9 The initial viscosity of the slurry was 8820 cps, and the viscosity of the slurry after storage for three months was 7232 cps, with a viscosity change rate of 18%.
[0146] The change curve of the conductive paste storage time at room temperature and the paste D90 is shown in Fig.10 The initial D90 of the slurry was 22.75 μm; after 3 months, the D90 of the slurry was 31.25 μm, and the change rate was 37%.
[0147] Conductivity test: the solid content of the slurry is 72%, the viscosity of the slurry is 10000-25000cps, the main material single crystal NCM532, carbon nanotube conductive slurry, and binder PVDF are put into the slurry mixing equipment at a mass ratio of 98.9:0.05:1 and fully mixed, and then coated on the surface of the PET film. The coating wet material thickness is 200μm. After drying at 100℃ for 1h, the volume resistivity is tested by a four-probe resistance tester. When the addition amount is 0.05% in the single crystal NCM523, the volume resistivity is 16.2Ω.cm. The information is shown in Table 1.
[0148] Example 2
[0149] (1) Preparation of dispersant gel
[0150] 7 parts of dispersant (polyvinylidene fluoride, PVDF) powder with a weight average molecular weight of 780000 g / mol was added to 93 parts of NMP (N-methylpyrrolidone), and after simple mechanical stirring and mixing, it was dispersed twice with a homogenizer at 60 MPa to obtain a 7% dispersant gel.
[0151] The viscosity of the dispersant gel solution was 5300 cps. The weight average molecular weight of the dispersant in the gel solution measured by high performance liquid chromatography was 686400 g / mol, and the dispersion coefficient was 2.1.
[0152] (2) Preparation of conductive paste
[0153] After adding 44 parts of dispersant gel to 54.6 parts of NMP solvent, 0.1 parts of onion-like fullerene was added. The onion-like fullerene selected was a cavity structure with an outer diameter of 60nm, an inner diameter of 55nm, and a layer number n=8; BET was 210m 2 / g;I G / I D is 1.7. The linear speed of the premixing equipment is 20 m / s, and the premixing time is 15 min to obtain a pre-dispersed liquid;
[0154] After 1.3 parts of carbon nanotubes were added to the pre-dispersed liquid, the pre-mixing equipment was used to pre-mix at 40 m / s for 20 minutes. After pre-mixing, homogenization was performed at a homogenization pressure of 60 MPa and the number of homogenizations was 13 times to obtain a carbon nanotube conductive slurry, wherein the composition of the selected carbon nanotubes was: 78% single-walled carbon nanotubes, 19% double-walled carbon nanotubes and 3% triple-walled carbon nanotubes.
[0155] The diameter of carbon nanotubes is 2.2nm; BET is 850m 2 / g; the G / D ratio of the carbon tube is 76; the purity of the carbon tube is 99.5%.
[0156] SEM images of carbon nanotubes and onion-like fullerenes in the conductive paste are shown in Figure 3 , TEM image see Figure 7 . Figure 3 The left picture in the middle is a low-magnification SEM image, and the right picture is a high-magnification SEM image. From the left picture, it can be seen that the carbon nanotubes are relatively long, about 35 μm in length. From the right picture, it can be seen that the onion-like fullerenes are significantly more numerous than in Example 1, with less agglomeration, and the distribution between the single-walled carbon nanotubes is still relatively uniform.
[0157] Figure 7 The middle left picture is a TEM picture of the SEM low-magnification morphology, and the right picture is a TEM picture of the SEM high-magnification morphology. From the low-magnification morphology on the left picture, it can be seen that the number of onion-like fullerenes is relatively small, and there is a small amount of onion-like fullerene aggregation in local areas; the high-magnification morphology on the right picture shows that the onion-like fullerene is 60nm spherical, and its information is detailed in Table 1.
[0158] The carbon nanotube conductive slurry obtained has a length of about 35 μm and a bundle width of about 120 nm. The G / D ratio after drying is 63. The change curve of the storage time and viscosity of the conductive slurry at room temperature is shown in FIG. Fig. 9 The initial viscosity of the slurry is 12500cps. After three months of storage, the viscosity of the slurry is 9375cps, and the viscosity change rate is 25%. The change curve of the conductive slurry storage time and slurry D90 at room temperature is shown in Fig.10 The initial D90 of the slurry was 24.58 μm; after 3 months, the D90 of the slurry was 32.27 μm, with a change rate of 31.3%. According to the conductivity test steps in Example 1, the volume resistivity of the slurry prepared in this example was measured to be 27.9 Ω.cm.
[0159] Example 3
[0160] (1) Preparation of dispersant gel
[0161] 10 parts of dispersant (polyvinylidene fluoride, PVDF) powder with a weight average molecular weight of 830000 g / mol was added to 90 parts of NMP (N-methylpyrrolidone), and after simple mechanical stirring and mixing, it was dispersed 3 times with a homogenizer at 60 MPa to obtain a 10% dispersant gel solution. The viscosity of the dispersant gel solution was 5600 cps, and the weight average molecular weight of the dispersant in the gel solution was 705500 g / mol and the dispersibility coefficient was 2.3 as measured by high performance liquid chromatography.
[0162] (2) Preparation of conductive paste
[0163] After adding 12.6 parts of dispersant gel to 86.77 parts of NMP solvent, 0.03 parts of onion-like fullerene was added. The onion-like fullerene selected was a cavity structure with an outer diameter of 30nm, an inner diameter of 26nm, and a layer number n=6; BET was 280m 2 / g;I G / I D The linear speed of the premixing equipment is 16 m / s, and the premixing time is 15 min to obtain a pre-dispersed liquid;
[0164] After 0.6 parts of carbon nanotubes are added to the pre-dispersed liquid, the pre-mixing equipment is used to pre-mix at 30m / s for 20min. After pre-mixing, homogenization is performed at a homogenization pressure of 50Mpa and the number of homogenizations is 6 times to obtain a carbon nanotube conductive slurry. Among them, the composition of the selected carbon nanotubes is: 73% single-walled carbon nanotubes, 23% double-walled carbon nanotubes and 4% triple-walled carbon nanotubes. The diameter of the carbon nanotubes is 2.9nm; BET is 780m 2 / g; the G / D ratio of the carbon nanotubes is 51; and the purity of the carbon nanotubes is 99.5%.
[0165] The carbon nanotube conductive slurry obtained has a length of about 42 μm and a bundle width of about 160 nm. The G / D ratio after drying is 42. The storage time and viscosity curve of the conductive slurry at room temperature are shown in FIG. Fig. 9 The initial viscosity of the slurry is 6300cps. After three months of storage, the viscosity of the slurry is 5040cps, and the viscosity change rate is 20%. The change curve of the conductive slurry storage time and slurry D90 at room temperature is shown in Fig.10 The initial D90 of the slurry was 20.89 μm; after 3 months, the D90 of the slurry was 27.81 μm, with a change rate of 33%.
[0166] Conductivity test: the solid content of the slurry is 72%, the viscosity of the slurry is 10000-25000cps, the main material single crystal NCM532, carbon nanotube conductive slurry, and binder PVDF are put into the slurry mixing equipment at a mass ratio of 98.9:0.05:1 and fully mixed, and then coated on the surface of the PET film. The coating wet material thickness is 200μm. After drying at 100℃ for 1h, the volume resistivity is tested by a four-probe resistance tester. When the addition amount is 0.05% in the single crystal NCM523, the volume resistivity is 32.6Ω.cm. The information is shown in Table 1.
[0167] Comparative Example 1
[0168] To prove that onion-like fullerenes can improve the length of carbon nanotubes in the conductive paste, the onion-like fullerenes in step (2) of Example 1 were removed, and the conductive paste was prepared as Comparative Example 1 with the other steps and materials unchanged. The information is shown in Table 1. The SEM images of the carbon nanotubes and onion-like fullerenes in the conductive paste of this comparative example are shown in Table 1. Figure 4 ,from Figure 4 It can be seen that compared with Example 1, since onion-like fullerenes are not added in Comparative Example 1, the carbon nanotubes in the final slurry are significantly shorter due to overdispersion in some processes, and the measured length is about 15μm. Due to the short length of the carbon tubes, their conductivity in the single crystal NCM523 is affected, and the volume resistivity is 58.8Ω.cm, which is significantly higher than that in Example 1.
[0169] The carbon nanotube conductive slurry obtained has a carbon nanotube length of about 15 μm and a tube bundle width of about 150 nm; the G / D after drying the slurry is 72. The change curve of the conductive slurry storage time and viscosity at room temperature is shown in Fig. 9 The initial viscosity of the slurry was 9100cps, and the viscosity of the slurry after three months of storage was 5460cps, with a viscosity change rate of 40%. Fig. 9 It can be seen that in Comparative Example 1, since onion-like fullerenes were not added, carbon nanotubes in the slurry agglomerated after a long storage time, and the slurry stability was worse than that in Example 1. The viscosity changed by 25% in the first month and 40% in three months.
[0170] The change curve of the conductive paste storage time at room temperature and the paste D90 is shown in Fig.10 The initial D90 of the slurry was 14.99 μm; after 3 months, the D90 of the slurry was 59.27 μm, with a change rate of 295%. Fig.10 It can be seen that in Comparative Example 1, due to the lack of onion-like fullerenes, the carbon nanotubes were over-grinded, resulting in a smaller initial D90 of the slurry. After 3 months of storage, the carbon nanotubes in the slurry agglomerated, and the slurry D90 changed by >50%.
[0171] The conductivity test was carried out according to the method in Example 1. When the addition amount was 0.05% in the single crystal NCM523, the volume resistivity was 58.8Ω.cm.
[0172] Comparative Example 2
[0173] To demonstrate the effect of onion-like fullerene addition on carbon nanotube conductive paste, in Comparative Example 2, the onion-like fullerene addition was 0.3%, and the other steps and materials were the same as in Example 1, and their information is shown in Table 1. The SEM images of carbon nanotubes and onion-like fullerene in the conductive paste of this comparative example are shown in Figure 5 From the figure, we can see that many onion-like fullerenes exist between carbon nanotubes, and onion-like fullerenes have certain agglomeration. This phenomenon is caused by the difficulty in dispersion when the content is high.
[0174] The TEM images of carbon nanotubes and onion-like fullerenes in this comparative example are shown in Figure 8 From the low-magnification TEM photo on the left, we can see that there are many large-sized onion-like fullerene agglomerates distributed between the carbon nanotubes, and the dispersion effect is poor. The TEM photo on the right shows agglomerates composed of many onion-like fullerenes. In the obtained carbon nanotube conductive slurry, the length of the carbon nanotube is about 18μm, and the width of the tube bundle is about 280nm; the G / D after the slurry is dried is 70. The change curve of the conductive slurry storage time and viscosity at room temperature is shown in Fig. 9 The initial viscosity of the slurry was 9600cps, and after three months of storage, the viscosity of the slurry was 6240cps, with a viscosity change rate of 35%. When the amount of onion-like fullerene added was large, it was difficult to disperse itself and there would be agglomeration, which reduced its lubrication and stabilization effect, resulting in a large change in the viscosity of the slurry after three months of storage, with a change rate of 35%.
[0175] The change curve of the conductive paste storage time at room temperature and the paste D90 is shown in Fig.10 The initial D90 of the slurry was 16 μm, and the D90 of the slurry after 3 months was 49.2 μm, with a change rate of 207%.
[0176] The conductivity test was carried out according to the method in Example 1. When the amount of the slurry added was 0.05% in the single crystal NCM523, the volume resistivity was 47.6Ω.cm. The volume resistivity of the slurry prepared in this comparative example was much greater than that in Example 1. This was because the amount of onion-like fullerene added in this comparative example was relatively large, and the onion-like fullerene agglomerated, which did not play a good lubricating role, resulting in the shortening of the carbon nanotubes, which reduced their conductivity in the single crystal 523 positive electrode.
[0177] Comparative Example 3
[0178] To demonstrate the effect of high-speed dispersion of dispersant colloid on the stability of carbon nanotube conductive paste. In comparative example 3, 8 parts of dispersant (polyvinylidene fluoride, PVDF) powder with a weight average molecular weight of 950,000 g / mol were added to 92 parts of NMP (N-methylpyrrolidone), and 8% dispersant colloid was obtained after simple mixing by conventional mechanical stirring. The viscosity of the dispersant colloid was 9600 cps, and the weight average molecular weight of the dispersant in the colloid was measured by high performance liquid chromatography to be 950,000 g / mol, and the dispersibility coefficient was 2.9. Other steps and materials were the same as in Example 1, and their information is shown in Table 1.
[0179] The length of the carbon nanotubes in the obtained carbon nanotube conductive slurry was about 19 μm, and the bundle width was about 260 nm. The G / D after the slurry was dried was 68. The change curve of the conductive slurry storage time and viscosity at room temperature is shown in Fig. 9 The initial viscosity of the slurry was 13500 cps. After three months of storage, the viscosity of the slurry was 9180 cps, and the viscosity change rate was 32%. Fig. 9 It can be seen that in Comparative Example 3, since the dispersant gel solution has not been subjected to high speed, its molecular weight distribution is uneven, the dispersibility coefficient of the dispersant in the dispersant gel solution is high, and the viscosity change of the slurry in the first month of storage is small, but the viscosity change rate in the second month has reached 29%, and the viscosity change rate in the third month is 32%; the change curve of the conductive slurry storage time and slurry D90 at room temperature is shown in Fig.10 The initial D90 of the slurry was 22.18 μm; after 3 months, the D90 of the slurry was 55.21 μm, and the change rate was 149%.
[0180] The conductivity test was carried out according to the method in Example 1. When the addition amount was 0.05% in the single crystal NCM523, the volume resistivity was 46.8Ω.cm. The volume resistivity of this comparative example is also much higher than that of Example 1. This may be because the dispersant colloid has not been subjected to high-speed dispersion treatment, and its viscosity is relatively large, resulting in poor dispersion of onion-like fullerenes and carbon nanotubes, relatively thick bundle width of carbon nanotubes, and high volume resistance. In addition, since the dispersant colloid has not been subjected to high-speed dispersion treatment, its dispersibility coefficient is relatively high, and the molecular weight distribution is more uneven. The dispersion effect on carbon nanotubes and onion-like fullerenes is worse than that of Example 1, resulting in a large viscosity change rate during the 3-month storage of the slurry. This comparative example shows that high-speed dispersion of the dispersant colloid has a more significant improvement in the storage stability of the slurry.
[0181] Table 1
[0182]
[0183]
[0184] In summary, the viscosity of the slurry in Examples 1-3 is relatively stable after being stored at room temperature for three months, with a change rate of less than 30%. In Comparative Example 1, the stability of the slurry is poor due to the lack of onion-like fullerenes, with a viscosity change rate of 25% in the first month and 40% in the third month; in Comparative Example 3, since the dispersant colloid has not undergone high-speed dispersion treatment, its dispersibility coefficient is relatively high, which also leads to poor storage stability of the conductive slurry. After three months of storage, the viscosity change rate is 32%. The present invention adds a certain amount of onion-like fullerenes to the conductive slurry, and the synergistic effect between the components is generated, which can effectively improve the re-agglomeration problem of carbon nanotubes after dispersion, thereby significantly improving the storage stability problem of the conductive slurry; at the same time, the dispersant is added to the slurry in the form of a highly dispersed colloid, which improves the dispersing effect of the dispersant on carbon nanotube bundles and onion-like fullerenes in the subsequent slurry preparation process, and further improves the storage stability of the slurry.
[0185] It should be understood that the above embodiments are exemplary and are not intended to include all possible implementations included in the claims. Various modifications and changes may be made on the basis of the above embodiments without departing from the scope of the present disclosure. Similarly, the various technical features of the above embodiments may be arbitrarily combined to form other embodiments of the present invention that may not be explicitly described. Therefore, the above embodiments only express several implementations of the present invention and do not limit the scope of protection of the patent of the present invention.
Claims
1. A conductive paste, characterized in that: Taking the total mass of the conductive paste as 100%, the conductive paste includes the following components in percentage by mass: Carbon nanotubes 0.45%-1.35% Onion-like fullerene 0.02%-0.15% Dispersant glue 12%-45% The balance was solvent 1.
2. The conductive paste according to claim 1, characterized in that: Taking the total mass of the conductive paste as 100%, the conductive paste includes the following components in percentage by mass: Carbon nanotubes 0.6%-1.30% Onion-like fullerene 0.02%-0.1% Dispersant glue 12.5%-37.5% The balance was solvent 1.
3. The conductive paste according to claim 1, characterized in that: The onion-shaped fullerene has an outer diameter of 5-80 nm and an inner diameter of 2-72 nm; Preferably, the onion-like fullerene has 3 to 10 layers and a specific surface area of 80 to 500 m 2 / g,I G / I D Is 1-5.
4. The conductive paste according to claim 1, characterized in that: The carbon nanotubes include single-walled carbon nanotubes and / or multi-walled carbon nanotubes; Preferably, the carbon nanotubes are a mixture of single-walled carbon nanotubes, double-walled carbon nanotubes and triple-walled carbon nanotubes; Preferably, the mass proportion of the single-walled carbon nanotubes is 70-95%, the mass proportion of the double-walled carbon nanotubes is 4-25%, and the mass proportion of the triple-walled carbon nanotubes is 1-5%; Preferably, the length of the carbon nanotubes in the conductive paste is 20-60 μm.
5. The conductive paste according to claim 1, characterized in that: The dispersant gel solution contains a dispersant, preferably, the dispersant gel solution contains a dispersant and a solvent 2; Preferably, the dispersant is selected from polyvinylidene fluoride; Preferably, the mass percentage of the dispersant in the dispersant colloid is 6-10%, and the weight average molecular weight of the dispersant in the dispersant colloid is 400000-1000000 g / mol; Preferably, the polydispersity coefficient of the dispersant in the dispersant gel is 1.5-2.5; Preferably, the viscosity of the dispersant colloid is 3000-8000cps; Preferably, the solvent 1 and the solvent 2 are independently selected from N-methylpyrrolidone.
6. The conductive paste according to claim 1, characterized in that: The viscosity of the conductive paste is 6000-13000 cps, and the D90 of the conductive paste is less than or equal to 60 μm; Preferably, after being stored at room temperature for 3 months, the viscosity change rate of the conductive paste is less than 30%, and the D90 change rate of the conductive paste is less than 50%.
7. The method for preparing the conductive paste according to any one of claims 1 to 6, characterized in that: The preparation method comprises: (1) mixing a dispersant gel, onion-like fullerene, and solvent 1 and pre-dispersing them to obtain a pre-dispersed liquid; (2) The carbon nanotubes are mixed with the pre-dispersed liquid, and then pre-mixed and homogenized to obtain the conductive paste.
8. The preparation method according to claim 7, characterized in that: In step (1), the preparation method of the dispersant glue solution comprises: dissolving the dispersant in solvent 2, and obtaining the dispersant glue solution after stirring and high-speed dispersion; Wherein, the pressure for controlling the high-speed dispersion is 50-120Mpa, and the number of times of performing the high-speed dispersion is 1-6 times; Preferably, the initial weight average molecular weight of the dispersant is 600000-1200000 g / mol; Preferably, before the stirring, the polydispersity coefficient of the dispersant in the solution is 2.5-5.5; Preferably, in step (1), the premixing line speed is controlled to be 10-30 m / s and the time is 10-20 min; Preferably, the solvent 1 and the solvent 2 are independently selected from N-methylpyrrolidone.
9. The preparation method according to claim 7, characterized in that: In step (2), the premixing line speed is controlled to be 20-80 m / s and the time is 10-20 min; Preferably, the homogenization pressure is 20-60 MPa, and the number of times is 4-15 times.
10. A conductive film, characterized in that: The conductive film comprises the conductive paste according to any one of claims 1 to 6 or the conductive paste obtained by the preparation method according to any one of claims 7 to 9.
11. A lithium ion battery, comprising the conductive paste according to any one of claims 1 to 6 or the conductive paste obtained by the preparation method according to any one of claims 7 to 9.